In-silico analysis of mt-CO1 gene of Taenia hydatigena sheep isolates - Celik, F.; Kilinc, S. Gunyakti; Kesik, H. Kaya; Ahmed, H.; Simsek, S. (Sciendo, 2021)
Taenia hydatigena is a tapeworm that affects herbivores in different regions of the world. Cysticercus tenuicollis (larvae of T. hydatigena), is prevalent in ruminants and pigs. In the current study, phylogenetic analysis of the published mt-CO1 gene of C. tenuicollis sheep isolates was analyzed using in-silico method and vertical and horizontal transmission at the global level by using a meta-analysis approach. A total of 82 mt-CO1 nucleotide sequences (339 bp) of C. tenuicollis sheep isolates from the NCBI database (Italy -Sardinia-, Iran, Palestine, Iraq, Finland, India and China) were used to investigate haplotype and genetic relationships. Tajima's D (-2,2984) value was negative for the mt-CO1 sequences signifying the population expansion and/or purifying selection. The highly negative Fu's Fs (-60,528) values determined for the sequences reflecting the existence of uncommon haplotypes. The mt-CO1 of C. tenuicollis haplotype network had 47 haplotypes arranged within a star-like configuration with a main haplotype, which encompassed 25.6 % of the total isolates. In the mt-CO1 haplotype network analyzed, there were 80.5 % unique single haplotype and highest ratio was observed in C. tenuicollis from sheep originating from Iran, followed by Sardinia, Palestine and Finland. If the current condition continues, genetic differences in T. hydatigena will be able to rise, and possible new strains and/or genotypes that may influence the host adaptation and life cycle of the parasite may emerge.
Keywords: Taenia hydatigena; Cysticercus tenuicollis; sheep; CO1; in-silico analysis